2020
DOI: 10.21307/pm-2020.59.2.009
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms As Indoor And Outdoor Air Biological Pollution

Abstract: Atmospheric air, including indoor air, is a basic factor affecting the proper functioning of the human body. Air pollution constitutes one of the main threats to the environments in which people live. World Health Orga-nization (WHO) and European Environment Agency (EEA) report that environmental risks such as air or water pollution have a significant impact on human health [26,108]. Air pollution includes all substances in the Earth's atmosphere that are not natural components, as well as natural substances i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 91 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…The concentration of bacteria indoors can be suppressed by improving room conditions through better hygiene, lighting, and ventilation, and by maintaining optimum room temperature and humidity [4]. Utilizing hospital cleaning staff for thorough cleaning, activating the air conditioner, and regularly monitoring temperature and humidity are some actionable routines to suppress indoor bacteria concentration.The installation of an air purifier is another thing to consider [20]. We found the total bacteria count was reduced upon biosterilizer activation, and the most significant reduction in concentration was located near the air purifier.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The concentration of bacteria indoors can be suppressed by improving room conditions through better hygiene, lighting, and ventilation, and by maintaining optimum room temperature and humidity [4]. Utilizing hospital cleaning staff for thorough cleaning, activating the air conditioner, and regularly monitoring temperature and humidity are some actionable routines to suppress indoor bacteria concentration.The installation of an air purifier is another thing to consider [20]. We found the total bacteria count was reduced upon biosterilizer activation, and the most significant reduction in concentration was located near the air purifier.…”
Section: Discussionmentioning
confidence: 85%
“…A high concentration of bacteria in the air increases the risk of infection as many harmful bacteria can live there, such as Staphylococcus aureus, Staphylococcus p., Neisseria m., Corynebacterium diphtheriae, hepatitis B virus, and cytomegalovirus [20]. The concentration of bacteria indoors can be suppressed by improving room conditions through better hygiene, lighting, and ventilation, and by maintaining optimum room temperature and humidity [4].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention that the outside air coming into both chambers had exactly the same properties, the flooring material in both chambers had the same composition and amount, and in Chamber A, an active plant-based system was place to evaluate its impact in the perceived IAQ. Regarding the RH levels, it is important to mention that any vegetation system generates extra humidity in the environment [33].…”
Section: Impact Of Temperature and Humidity In Human Perceptionmentioning
confidence: 99%
“…Previous studies have shown that perceptual reaction to different odors varies according to individual sensitivity, and in general, when the participants do not know the source of the smell or if they feel that the smell is potentially hazardous, they tend to reject the smell and show their discomfort [38]. Finally, the fact that an active plant-based system was introduced in Chamber A may introduce other pollutants and compounds into the chamber [20], such as mold [33].…”
Section: Acceptability Intensity Odour Recognition and Preferencementioning
confidence: 99%
“…The presence of pathogenic organisms (viruses, bacteria or fungi) has a significant impact on health. It can cause long-term effects, worsening the quality of life for many months or years, even after infection, and in extreme cases, lead to disability or death [1,5,8,9,[11][12][13][14][15]. Currently, hospital risks are of particular concern.…”
Section: Introductionmentioning
confidence: 99%